A willow UDP-glycosyltransferase involved in salicinoid biosynthesis. (28th November 2020) - Kulasekaran, Satish; Cerezo-Medina, Sergio; Harflett, Claudia; Lomax, Charlotte; de Jong, Femke; Rendour, Amelie; Ruvo, Gianluca; Hanley, Steven J; Beale, Michael H; Ward, Jane L
Abstract : We report the cloning and functional characterization of willow glycosytransferase enzymes involved in the biosynthesis of salicinoids, metabolites with a historic role in the development of aspirin. Abstract: The salicinoids are phenolic glycosides that are characteristic secondary metabolites of the Salicaceae, particularly willows and poplars. Despite the well-known pharmacology of salicin, that led to the development of aspirin >100 years ago, the biosynthetic pathways leading to salicinoids have yet to be defined. Here, we describe the identification, cloning, and biochemical characterization of SpUGT71L2 and SpUGT71L3—isozymic glycosyltransferases from Salix purpurea— that function in the glucosylation of ortho -substituted phenols. The best substrate in vitro was salicyl-7-benzoate. Its product, salicyl-7-benzoate glucoside, was shown to be endogenous in poplar and willow. Together they are inferred to be early intermediates in the biosynthesis of salicortin and related metabolites in planta . The role of this UDP-glycosyltransferase was confirmed via the metabolomic analysis of transgenic plants produced by RNAi knockdown of the poplar orthologue (UGT71L1) in the hybrid clone Populus tremula×P. alba, INRA 717-1B4.